James Dudley Morgan collection of Digges-L'Enfant-Morgan papers - Morgan, James Dudley, 1862-1919.; Digges, Thomas Attwood, 1742-1821.; Digges, William Dudley, 1790-1830.; L'Enfant, Pierre Charles, 1754-1825.
Correspondence, accounts, commissions, notes, and other papers relating to Pierre Charles L'Enfant's career as an architect-engineer and to his personal and family life. Includes material concerning the design of the city of Washington and the conflict between L'Enfant and commissioners Daniel Carroll, Thomas Jefferson, and Thomas Johnson. Also includes material pertaining to the Society of the Cincinnati, the Society for Establishing Useful Manufactures, Robert Morris's home in Philadelphia, Fort Mifflin, Philadelphia, Pa., and Fort Washington, Md. Includes papers of the Digges family of Prince Georges County, Md., especially Thomas Atwood Digges and William Dudley Digges.
Correspondents include Daniel Carroll of Duddington, Alexander Hamilton, Thomas Jefferson, Thomas Johnson, the marquis de Lafayette, Tobias Lear, James Monroe, Robert Morris, Isaac Roberdeau, the baron von Steuben, David Stuart, and George Washington.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Physician of Washington, D.C.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carroll, Daniel, -- 1764-1849.; Carroll, Daniel, -- 1764-1849 -- Correspondence; Hamilton, Alexander, -- 1757-1804 -- Correspondence; Jefferson, Thomas, -- 1743-1826.; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Johnson, Thomas, -- 1732-1819.; Johnson, Thomas, -- 1732-1819 -- Correspondence; Lafayette, Marie Joseph Paul Yves Roch Gilbert Du Motier, -- marquis de, -- 1757-1834 -- Correspondence; Lear, Tobias, -- 1762-1816 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Morris, Robert, -- 1734-1806 -- Correspondence; Roberdeau, Isaac, -- 1763-1829 -- Correspondence; Steuben, Friedrich Wilhelm Ludolf Gerhard Augustin, -- Baron von, -- 1730-1794 -- Correspondence; Stuart, David -- Correspondence; Washington, George, -- 1732-1799 -- Correspondence; Digges family; L'Enfant family; Society for Establishing Useful Manufactures; Society of the Cincinnati; Architecture, Domestic -- Pennsylvania -- Philadelphia; City planning -- Washington (D.C.); Fortification -- Maryland; Fortification -- Pennsylvania; Manufacturing industries -- United States; Military bases -- Maryland; Military bases -- Pennsylvania; Fort Mifflin (Philadelphia, Pa.); Fort Washington (Md. : Fort); Prince Georges County (Md.) -- Social life and customs; Physicians